2015
DOI: 10.1080/19440049.2015.1045557
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 4(5)-methylimidazole in carbonated beverages by isotope-dilution liquid chromatography-tandem mass spectrometry

Abstract: The purpose of this study was to develop a method to quantify 4(5)-methylimidazole (4-MEI), a suspected carcinogen, in carbonated beverages by simple sample dilution and isotope-dilution reverse-phase LC-MS/MS. Isotope dilution using hexa-deuterated methylimidazole (d6-4-MEI) was used to quantify native 4-MEI and to assess matrix effects quantitatively. The accuracy of the method was assessed by intentionally fortifying a negative control sample at three doses: low, medium and high (replicates of n = 5 each) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
2
2
0
1
Order By: Relevance
“…The kilned roasted malts used and/or caramel color addition may be the possible sources of the presence of 2‐MeI and 4‐MeI in the dark beers. Our data on the contents of 4‐MeI in the dark beers were also in good agreement with the previously reported values (Klejdus and others ; Cunha and others ; Ratnayake and others ). It has been reported that the 4‐MeI contents in Canada dark beers were in the range of 12.7 to 673 μg/L (Ratnayake and others ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The kilned roasted malts used and/or caramel color addition may be the possible sources of the presence of 2‐MeI and 4‐MeI in the dark beers. Our data on the contents of 4‐MeI in the dark beers were also in good agreement with the previously reported values (Klejdus and others ; Cunha and others ; Ratnayake and others ). It has been reported that the 4‐MeI contents in Canada dark beers were in the range of 12.7 to 673 μg/L (Ratnayake and others ).…”
Section: Resultssupporting
confidence: 93%
“…Our data on the contents of 4‐MeI in the dark beers were also in good agreement with the previously reported values (Klejdus and others ; Cunha and others ; Ratnayake and others ). It has been reported that the 4‐MeI contents in Canada dark beers were in the range of 12.7 to 673 μg/L (Ratnayake and others ). The 4‐MeI contents in dark beers obtained from Portugal, Spain, and France markets were in the range of 3 to 424 μg/L (Cunha and others ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Xu et al (2015) encontraram 4-MEI em refrigerantes e refrigerantes contendo o corante caramelo IV em variações de 0,00013 a 0,00034 mg/mL. Ratnayake et al (2015) observaram variações de 0,0000097 a 0,000641 mg/mL de 4-MEI em diferentes refrigerantes de cola. Cunha et al (2016) avaliaram a presença de 4-MEI em diferentes tipos de café comercializados em Portugal.…”
Section: Resultsunclassified
“…Several methods have been developed to determine 4-MeI based on thin layer chromatography (Rabe et al, 1988), fluorimetry (Wu et al, 2016), capillary electrophoresis (Petruci et al, 2013), or high performance liquid chromatography (HPLC) coupled with ultraviolet light (UV) (Ratnayake et al, 2015). However, these methods require a labor and time-consuming sample pretreatment and have poor sensitivity.…”
Section: Introductionmentioning
confidence: 99%